Primary experiences and discontinuities of remembrance: notes from a text by Reinhart Koselleck (Tempo e Argumento, 2017)
This article takes as its starting point a text byReinhart Koselleck on the theme of memory,which analyzes supposed discontinuities betweenprimary experiences and secondary forms ofremembrance. Although this is a specific text andwe do not intend to see its statements asfoundations of a supposed author’s thought as awhole, we point out some potential relations withtheses found in his other works. Then, some of hisformulations are brought to a rather strictlyepistemological level and compared to theses byauthors such as Aleida Assmann, Joël Candau,Hannah Arendt, and Paul Ricoeur. The goal, in thiscase, is just mapping some problems regarded asrelevant when dealing with the relations betweenhistory, memory, truth, and justice, without anyambition of solving them.Keywords: Koselleck, Reinhart; Memory;Experience.